Analysis of Marine Planktonic Cyanobacterial Assemblages From Mooriganga Estuary, Indian Sundarbans Using Molecular Approaches - Bhadury, Punyasloke; Singh, Tarkeshwar (Frontiers in Marine Science, 2020)
The ecological significance of marine planktonic cyanobacteria in mangrove ecosystems is not well understood from the context of community structure and function. In this study, members of the marine planktonic cyanobacterial communities were elucidated based on 16S rRNA sequencing (clone libraries and Illumina sequencing) and microscopic approaches from the Sundarbans Biological Observatory Time Series (SBOTS) stations Stn1 and Stn 3 located in Mooriganga estuary over six months representing monsoon and post-monsoon seasons of 2012. In total 222 sequences were marine planktonic cyanobacteria-like and were dominated by three major clades of Synechococcus-like 16S rRNA sequences (160 sequences). There was clear dominance of Synechococcus sp. KORDI-78 like sequences (71 sequences) in both monsoon and post-monsoon seasons from the study area. Although in very low numbers, other cyanobacterial sequences showing taxonomic affiliation with members of Chroococcales, Pleurocapsales, Oscillatoriales and Stigonematales were also encountered. The presence of some of the representative genera belonging to the above Orders were reconfirmed by bright field microscopy from both stations of SBOTS. Presence of four novel clades of planktonic cyanobacteria were also confirmed from the study area based on molecular phylogeny thereby indicating unexplored cyanobacterial diversity is high in Sundarbans. Illumina sequencing undertaken for both stations of SBOTS in one of the monsoon months of 2014 (July) revealed low abundance of cyanobacteria-like sequences (2349 out of 4276863 pair-end reads) and dominance of KORDI-78 like sequences. Principal component analysis showed that dissolved nutrients, transparency and salinity influenced the observed marine planktonic cyanobacterial assemblages of Sundarbans. There was overall dominance of Synechococccus-like 16S rRNA sequences confirming the importance of small-sized picocyanobacteria cells and their ecological importance in export of carbon in mangrove ecosystems.